Study of regulatory requirements for the conduct of bioequivalence studies in US, Europe, Canada, India, ASEAN and SADC countries: Impact on generic drug substitution - Nitika Kaushal, Sachin Kumar Singh, Monica Gulati, Yogyata Vaidya, Munish Kaushik (Journal of Applied Pharmaceutical Science, 2016)
In the last one decade, due to expiry of patented products as well as their exclusivity period, a drastic decline of branded pharmaceutical products and up streaming of generic drug market has been observed in developed as well as developing nations. This up rise in generic drug market is expected to rise in future till the arrival of new brand in market. This prevailing conditions could result in proliferation of generic drug manufacturing companies. The fact that generics do not undergo thorough extensive trials like innovator drugs, fuels further fears regarding their inferiority. Moreover, due to the hard competition amongst various companies to market their generics, the frequency of fraud and corruption have embarked doubts in consumers mind to reality. In order to blow away the doubts and re-establishing the credibility of generics in market, bioequivalence (BE) guidelines with stricter regulation should be the demand. The present study highlights the relevant regulatory guidelines for the conduct of bioequivalence studies in US, Europe, Canada, India, South Africa and South East Asian Nations. A comparative study of the differences in study design and specifications have also been addressed.
Keywords: Innovator drought, Brand erosion, Patent Cliff, branded products, bioequivalence studies, pharma-emerging nations.